Efficacy and safety of single-pill amlodipine/losartan versus losartan in patients with inadequately controlled hypertension after losartan treatment: a multicenter, double-blind, randomized phase III clinical trial - Zhang, Shuyang; Li, Ying; Xu, Xin; Xu, Rui; Zhang, Linchao; Wan, Xiaoqun; Yao, Zhuhua; Sun, Yuemin; Liu, Yong; Bin, Jianping; Wang, Zhen; Li, Shuren; et al. (Frontiers in Cardiovascular Medicine, 2023)
Objective Single-pill amlodipine besylate (AML) plus losartan (LOS) has been used to treat inadequately controlled hypertension after antihypertensive monotherapy; however, relevant data in China are limited. This study aimed to compare the efficacy and safety of single-pill AML/LOS and LOS alone in Chinese patients with inadequately controlled hypertension after LOS treatment. Methods In this multicenter, double-blind, randomized, controlled phase III clinical trial, patients with inadequately controlled hypertension after 4 weeks of LOS treatment were randomized to receive daily single-pill AML/LOS (5/100 mg, AML/LOS group, N = 154) or LOS (100 mg, LOS group, N = 153) tablets for 8 weeks. At weeks 4 and 8 of treatment, sitting diastolic and systolic blood pressure (sitDBP and sitSBP, respectively) and the BP target achievement rate were assessed. Results At week 8, the sitDBP change from baseline was greater in the AML/LOS group than in the LOS group (−8.84 ± 6.86 vs. −2.65 ± 7.62 mmHg, P < 0.001). In addition, the AML/LOS group also showed greater sitDBP change from baseline to week 4 (−8.77 ± 6.60 vs. −2.99 ± 7.05 mmHg) and sitSBP change from baseline to week 4 (−12.54 ± 11.65 vs. −2.36 ± 10.33 mmHg) and 8 (−13.93 ± 10.90 vs. −2.38 ± 12.71 mmHg) (all P < 0.001). Moreover, the BP target achievement rates at weeks 4 (57.1% vs. 25.3%, P < 0.001) and 8 (58.4% vs. 28.1%, P < 0.001) were higher in the AML/LOS group than those in the LOS group. Both treatments were safe and tolerable. Conclusion Single-pill AML/LOS is superior to LOS monotherapy for controlling BP and is safe and well tolerated in Chinese patients with inadequately controlled hypertension after LOS treatment.